Mathematical model for the expulsion of salt and water by the kidney [electronic resorce] - Nur Raihan Abdul Salim, 1985-; Fakulti Sains (2015)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2015